Out-migration and attrition of physicians and dentists before and after EU accession (2003 and 2011): The case of Hungary - Júlia Varga (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2016)
This paper employs a large-scale, individual-level, panel dataset to analyse the effect of EU accession on the probability of out-migration on the part of Hungarian physicians and dentists between 2003 and 2011. The study uses event history modelling and competing risk models. The results show that EU accession did not at the time affect the probability of the out-migration on the part of Hungarian medical doctors, while after the end of the transitional period of restrictions on the free movement of labour from the new EU member states to Austria and Germany (May 2011), the probability of doctors' migration increased considerably, as it did (for other reasons) starting in the spring of 2010. We also found that more than half of those medical doctors who left the country during the observation period returned sometime later. Results also show that in Hungary, in addition to migration, the attrition of doctors' numbers is also a severe problem. It seems that shortages of healthcare professionals are not only due to high outward migration but may also be attributed to other problems in the Hungarian health system. Nevertheless, outward migration plays an important and growing role in the phenomenon.
Keywords: C41; C55; I10; J4; J40; J45; J60; J61; 330; medical doctors' migration; competing risk model